A study of effectiveness and adherence between fixed combination dorzolamide /timolol maleate and non-fixed dorzolamide and timolol xe in open angle glaucoma - Rasid, Noor Khairul (2015)

(untitled)
INTRODUCTION The effective treatment and adherence to medication are important factors for successful management of glaucoma. Many evidences showed that lowering the IOP could prevent and halt the progression of optic nerve damage and visual field loss. OBJECTIVES To determine and compare the pressure lowering effects and adherence score between fixed-combination dorzolamide/ timolol maleate (FCDT) and non-fixed combination dorzolamide and timolol XE (NFDT) in open angle glaucoma. METHODS This randomised controlled trial, parallel groups and single-blinded study involved 55 patients of OAG. Patients were randomised to FCDT group who received fixedcombination dorzolamide/ timolol maleate and NFDT group that received concomitant dorzolamide and timolol XE for 3 months. Pre-study run-in timolol was given for 2 weeks. Baseline IOP was taken in the morning. Patients were follow-up at month 1 and month 3. IOP and safety of medication were assessed during follow-up. The adherence score consists of percentage of eye drops used based on bottle weight measurement, Glaucoma Medication Adherence Self-Efficacy Scale and Subjective Drug Adherence Score were recorded at month 3 follow-up. Data were analyzed using repeated measures ANOVA, independent t-test Pearson Chi Square test. RESULTS The demographic data were similar between the groups. FCDT and NFDT were statistically significant reduced the IOP at month 1 and month 3 with mean IOP reduction at month 1, 4.9 mmHg with 95% confidence interval ( 4.0 to 5.9) in FCDT, 4.9 ( 95% CI 4.0 to 5.8) mmHg in NFDT, at month 3 were 5.2 ( 95% CI 4.2 to 6.2) mmHg in FCDT and 4.9 ( 95% CI 3.9 to 5.8) mmHg in NFDT. The mean percentage of IOP difference between treatments groups at one month and three months were no significant different. There was no significant difference of mean total adherence score between the groups. CONCLUSION The pressure lowering effects of fixed-combinations dorzolamide/ timolol maleate and non-fixed combination dorzolamide and timolol XE was comparable. Both provide a significant reduction of IOP at one month and three months treatment. The total adherence score was high in both treatment groups and comparable.